1992
DOI: 10.1021/np50086a006
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Eriobotrya japonica. A Study of Their Antiviral Properties

Abstract: The CHCl3 extract of Eriobotrya japonica from an Italian source was shown to contain four new triterpene esters, namely, 23-trans-p-coumaroyltormentic acid [1], 23-cis-p-coumaroyltormentic acid [2], 3-O-trans-caffeoyltormentic acid [3], and 3-O-trans-p-coumaroylrotundic acid [4], in addition to three common ursolic acid derivatives 5, 6, and 7. An investigation of the antiviral properties of compounds 1-7 revealed that only 3 significantly reduced rhinovirus infection. The compounds were ineffective towards hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 18 publications
1
48
0
1
Order By: Relevance
“…Among Chinese medicine preparations, Eriobotrya japonica folia are an ingredient in Shini-seihai-to and Biwayo-to used as antiphlogistic, analgesic, antitussive, and expectorant agents. Recently, the blood sugar-reducing 9-11) and antiphlogistic actions 12,13) of Eriobotrya japonica folia have also been reported. On the other hand, Eriobotrya japonica seeds, like those of apricots and peaches of the same genus (Rosaceae), contain amygdalin as the main constituent; therefore, they were used as a substitute medication for the latter seeds in prewar Japan.…”
mentioning
confidence: 99%
“…Among Chinese medicine preparations, Eriobotrya japonica folia are an ingredient in Shini-seihai-to and Biwayo-to used as antiphlogistic, analgesic, antitussive, and expectorant agents. Recently, the blood sugar-reducing 9-11) and antiphlogistic actions 12,13) of Eriobotrya japonica folia have also been reported. On the other hand, Eriobotrya japonica seeds, like those of apricots and peaches of the same genus (Rosaceae), contain amygdalin as the main constituent; therefore, they were used as a substitute medication for the latter seeds in prewar Japan.…”
mentioning
confidence: 99%
“…japonica leaves contain triterpenes, sesquiterpenes, flavonoids, tannins, and amygdalin [1,2]. Among them, the triterpenes from E. japonica leaves might be expected to have potent bioactivities in vivo and in vitro [3].…”
Section: Hplc Fingerprinting Of Triterpenes In Eriobotrya Japonica Lementioning
confidence: 99%
“…The dried leaves of E. japonica are used in Japanese Kampo medicines and Traditional Chinese Medicines (TCM) for chronic bronchitis, cough, skin disease, inflammation, and diabetes. Previous phytochemical investigations have demonstrated that E. japonica leaves contain triterpenes, sesquiterpenes, flavonoids, tannins, and amygdalin [1,2]. Among them, novel biological properties of triterpenes, such as the attenuation of glycosylated serum protein, total cholesterol, and triglyceride level in diabetic mice have been reported [3].…”
Section: Introductionmentioning
confidence: 99%
“…비파 잎에는 다양한 terpenoid (Nazato et al 1984)와 플라보노이드 (Jung et al 1999 (Nazato et al 1994;Jung et al 1994;Taniguchi et al 2002). 이 밖에도 비파 잎, 씨 또는 과육에 다량 함유되어 있는 유용한 화합물들의 항산화효과 (Jung et al 1994;Koba et al 2007;Lee et al 2009), 항 당뇨효과 (Chen et al 2008), 항염증 및 항암효과 Banno et al 2005;Huang et al 2007), 항바이러스효과 (De Tommasi et al 1992 Seedless fruit.…”
Section: 서론unclassified